JOB SATISFACTION IN NURSES WORKING IN TERTIARY LEVEL HEALTH CARE SETTINGS OF ISLAMABAD, PAKISTAN - Bahalkani, Habib Akhtar; Kumar, Ramesh; Lakho, Abdul Rehman; Mahar, Benazir; Mazhar, Syeda Batool; Majeed, Abdul (Journal of Ayub Medical College Abbottabad, 2011)
Background: Job satisfaction greatly determines the productivity and efficiency of human resource for health. It literally means: ’˜the extent to which Health Professionals like or dislike their jobs’. Job satisfaction is said to be linked with employee’s work environment, job responsibilities, and powers; and time pressure among various health professionals. As such it affects employee’s organizational commitment and consequently the quality of health services. Objective of this study was to determine the level of job satisfaction and factors influencing it among nurses in a public sector hospital of Islamabad. Methods: A cross sectional study with self-administered structured questionnaire was conducted in the federal capital of Pakistan, Islamabad. Sample included 56 qualified nurses working in a tertiary care hospital. Results: Overall 86% respondents were dissatisfied with about 26% highly dissatisfied with their job. The work environments, poor fringe benefits, dignity, responsibility given at workplace and time pressure were reason for dissatisfaction. Poor work environment, low salaries, lack of training opportunities, proper supervision, time pressure and financial rewards reported by the respondents. Conclusion: Our findings state a low level of overall satisfaction among workers in a public sector tertiary care health organization in Islamabad. Most of this dissatisfaction is caused by poor salaries, not given the due respect, poor work environment, unbalanced responsibilities with little overall control, time pressure, patient care and lack of opportunities for professional development. Keywords: Job, satisfaction, healthcare organization, nursing staff, health, environment, pressure, responsibility, poor salaries